Overcoming Institutional Voids - Gao, Cheng; Zuzul, Tiona; Jones, Geoffrey; Khanna, Tarun (Strategic Management Journal, 2017)
[Research summary: Emerging markets are characterized by underdeveloped institutions and frequent environmental shifts. Yet, they also contain many firms that have survived over generations. How are firms in weak institutional environments able to persist over time? Motivated by 69 interviews with leaders of emerging market firms with histories spanning generations, we combine induction and deduction to propose reputation as a meta-resource that allows firms to activate their conventional resources. We conceptualize reputation as consisting of prominence, perceived quality, and resilience, and develop a process model that illustrates the mechanisms that allow reputation to facilitate survival in ways that persist over time. Building on research in strategy and business history, we thus shed light on an underappreciated strategic construct (reputation) in an undertheorized setting (emerging markets) over an unusual period (the historical long run). Managerial summary:Why are some firms able to persistently survive in challenging, uncertain, and underdeveloped business environments? To explore this question, we analyze in-depth interviews with leaders of emerging market firms that have survived over decades and even centuries. We find that firm reputation is a key strategic driver, and propose new ideas about the ways through which reputation facilitates survival. We elaborate how a favorable reputation allows a firm to more fully utilize its existing resources by decreasing uncertainty. We also propose that reputation has offensive and defensive properties that make it valuable to firms during both positive and negative economic cycles. Finally, we discuss why a reputation-based source of competitive advantage is hard to imitate, and outline three general approaches for building reputation.]